2006
DOI: 10.1287/mnsc.1040.0473
|View full text |Cite
|
Sign up to set email alerts
|

Up Close and Personal: Investor Sophistication and the Disposition Effect

Abstract: This paper analyzes the trading records of a major discount brokerage house to investigate the disposition effect, the tendency to sell stocks that have appreciated in price (winners) sooner than stocks that trade below the purchase price (losers). In contrast to previous research that has demonstrated the disposition effect by aggregating across investors, our main objective is to identify differences in the disposition bias across individuals and explain this in terms of underlying investor characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
388
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 706 publications
(438 citation statements)
references
References 44 publications
45
388
5
Order By: Relevance
“…Summers and Duxbury (2012) demonstrate that emotional responses such as regret are a necessary cause of disposition effects. The effect is confirmed for private investors (Odean, 1998;Dhar and Zhu, 2006), professional traders (Ferris et al, 1988, Garvey andMurphy, 2004), house owners (Genesove and Mayer, 2001), and students (Weber and Camerer, 1998). Recent experiments have demonstrated that nudging approaches help to debias the disposition effect of individuals.…”
Section: Introductionmentioning
confidence: 92%
“…Summers and Duxbury (2012) demonstrate that emotional responses such as regret are a necessary cause of disposition effects. The effect is confirmed for private investors (Odean, 1998;Dhar and Zhu, 2006), professional traders (Ferris et al, 1988, Garvey andMurphy, 2004), house owners (Genesove and Mayer, 2001), and students (Weber and Camerer, 1998). Recent experiments have demonstrated that nudging approaches help to debias the disposition effect of individuals.…”
Section: Introductionmentioning
confidence: 92%
“…4.1), several contributions lacking an observable measure of financial capabilities exploit this evidence and use respondents' demographics in order to capture their financial literacy. Corresponding proxies for financial sophistication used in the literature include (disposable) income and wealth (Dhar and Zhu 2006;Vissing-Jorgensen 2003;Calvet et al 2007Calvet et al , 2009) as well as age (Calvet et al 2007(Calvet et al , 2009Georgarakos and Pasini 2011), educational attainment (Christiansen et al 2008;Calvet et al 2007Calvet et al , 2009), professional status (Calvet et al 2009), and even IQ (Grinblatt et al 2011(Grinblatt et al , 2012. Likewise, both Chalmers and Reuter (2012) and Hackethal et al (2012) use subsets of these demographics to proxy for financial literacy in their analyses.…”
Section: Socio-demographic Proxiesmentioning
confidence: 99%
“…The effectiveness of such programs have been evaluated through, among others, individuals" portfolio diversification [4], extents of the disposition effect [5] and retirement planning [6]. The main problem associated with low level of financial literacy is that individuals can suffer credit problems which may lead to bankruptcy.…”
Section: A Financial Literacymentioning
confidence: 99%